2014
DOI: 10.1140/epjd/e2014-50146-y
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian structure of a drift-kinetic model and Hamiltonian closures for its two-moment fluid reductions

Abstract: We address the problem of the existence of the Hamiltonian structure for an electrostatic driftkinetic model and for the related fluid models describing the evolution of the first two moments of the distribution function with respect to the parallel velocity. The drift-kinetic model, which accounts for background density and temperature gradients as well as polarization effects, is shown to possess a noncanonical Hamiltonian structure. The corresponding Poisson bracket is expressed in terms of the fluid moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…Recent results, on the other hand, concern the identification of closure relations that, when inserted into the bracket of the fluid moments, truncate it in such a way that the resulting bracket is still a Poisson bracket. In the case when the parent model is a drift-kinetic one, it has been shown that the adiabatic closure is the only one possessing this property [28,29]. Linear closures, on the other hand, are those selected for drift and gyrokinetic models in the "δf approximation " [28,30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent results, on the other hand, concern the identification of closure relations that, when inserted into the bracket of the fluid moments, truncate it in such a way that the resulting bracket is still a Poisson bracket. In the case when the parent model is a drift-kinetic one, it has been shown that the adiabatic closure is the only one possessing this property [28,29]. Linear closures, on the other hand, are those selected for drift and gyrokinetic models in the "δf approximation " [28,30].…”
Section: Introductionmentioning
confidence: 99%
“…Obvious examples in this context would be toroidal geometry , magnetic, temperature and density equilibrium gradients (although the latter have already been partially treated in Ref. [12]). Perhaps even more fundamental is the problem of considering Hamiltonian closures at higher-order moments.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the functionals of interest will be of the kind F (P i 00 , P i 10 , P i 01 · · · P i M N , P e 00 , P e 10 , P e 01 · · · P e M N ) and will no longer depend on the infinite set of moments. The operation (12) between two such functionals, however, is not closed, in the sense that {F, G}, in general, will not be again a functional of the same kind, but it will depend also on moments of order higher than M (N ) in the parallel (perpendicular) direction. In order to obtain a closed system, the way we follow is that of modifying the Poisson bracket, imposing that such extra higher order moments be functions of the first M (N ) moments in the parallel (perpendicular) direction.…”
Section: Derivation Of the Hamiltonian Gyrofluid Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We remark that in Ref. [142], the above results were generalized to the case where the drift-kinetic distribution function is given by the sum of a perturbation with a non-uniform Maxwellian, thus leading to a Hamiltonian two-moment extension of the Charney-Hasegawa-Mima equation for drift waves.…”
Section: Two and Three-moment Drift-fluid Modelsmentioning
confidence: 94%